The handy guide to New Testament Greek: grammar, syntax, and diagramming - Huffman, Douglas S. (Kregel Academic, 2012)
Introduction -- Part 1 : Greek grammar reminder -- Part 2 : Greek syntax summaries -- Part 3 : Phrase diagramming.